Relevance of Religious Education in Students’ Development - Chidi Ilechukwu, Leonard (International Journal of Psychosocial Rehabilitation, 2021)
The goal of this research paper was to examine the relevance of Religious Education in students’ development. The research methodology involved conceptual analyses of grey literature, relevant websites and journal publications. Results show that several reasons have been stated to justify the need for Religious Education including that it is for moral education as well as for the promotion of understanding and respecting of other religions and beliefs. Religious Education as a school subject in many parts of the world seems to have three major strands which include assisting students to develop knowledge and understanding of religious beliefs and practices, contributing to students’ spiritual development, and equipping students with positive attitudes and skills for exploring and responding to religion. Evidence from literature also suggests that Religious Education is an essential component of a broad and balanced education whose focal point in the curriculum is to promote students’ spiritual, moral, social and cultural development and values. Therefore, when developing a Religious Education curriculum, schools should consider national and regional disparities in cultural and religious experiences.